The Determinants of Capital Structure: Evidence from the Turkish Manufacturing Sector - Songul KAKILLI ACARAVCI (International Journal of Economics and Financial Issues, 2015)
This study investigates the determinants of capital structure in Turkey by using panel data methods. The sample period spans from 1993 to 2010 for 79 firms in the manufacturing sector traded on the Istanbul Stock Exchange. The base model was expanded with firm size and sector-specific effects. This study compares also effects on capital structure according to sectors and firm size of variables used in models. Growth opportunities, size, profitability, tangibility and non-debt tax shields are used as the firm-specific variables that affect a firm’s capital structure decision. Empirical results present that there are significant relationships between growth opportunities, size, profitability, tangibility and leverage variables. But non-debt tax shields explanatory variable has insignificant effect on leverage 1 (book value of total debt / total assets) variable. Growth opportunity has effect on capital structure that this result supports the trade-off theory. Size, profitability and tangibility have effects and support the pecking order theory. On the other hand, profitability and growth opportunity variables have more significant effects than other variables on Leverage 1 and Leverage 2 (book value of total debt / book value of equity) for all sectors. Furthermore, in two leverage models, profitability variable of small and large firm groups has effect on capital structure and there is no a significant difference between two groups.